Hubungan antara Intensitas Menonton Tayangan Televisi Berisi Kekerasan, Persepsi terhadap Keharmonisan Keluarga, Jenis Kelamin, dan Tahap Perkembangan dengan Kecenderungan Agresivitas Remaja: The Relationship between the - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 2003)
This research aims to examine the relationship between the intensity of watching violence on television, the perception of family harmoniouness, with the aggressive tendencies of adolescence. This research also intends at knowing the differences in the aggressive tendencies of adolescence based on sex and phases of development The research subjects were 180 Senior High School (SMU) Bonaventura and Sint Louis at the Kotamadya Madiun, including 93 boys and 87 girls. Data was collected using questionnaires, those were aggressive tendencies of adolescence questionnaire, intensity of watching violence on television questionnaire, and perception of family harmoniousness questionnaire. Research data are analyzed using regression analysis, and analysis of variance. The results of the research show that: (1) there were positive and very significant correlation between the intensity of watching violence on television and the aggressive tendencies of adolescence fr 1 = 0,375